THE BENEFITS OF PHYSIOTHERAPY IN ALZHEIMER’S DISEASE SYMPTOMS - Graebin, André (Health and Society, 2023)
Introduction: The Alzheimer’s Disease is a progressive condition that affects the memory and other cognitive functions, impactaring negatively the the life of patients and their relatives. The physical therapy is an important alley in the treatment of these individuals, by aiming to improve their autonomy, well-being and independency. Objective: To show the benefits of the physical therapy treatment in patients with Alzheimer. Method: It was performed a bibliographic review research utilizing the Google Scholar, SciELO and PubMed databases in Portuguese, Spanish and English languages. Conclusion: It was found that the physical therapy is of high importance for the life quality maintenance in the population affected by the Alzheimer’s Disease, because it presents benefits in physical capabilities and motor skills such as: improved flexibility, strength gain, improved cardiovascular capacity, balance and better cognition.